Safety supports on employee safety voice - Nuri Herachwati; Jovi Sulistiawan; Zainiyah Alfirdaus; Bagus Anggara; Muhammad Atsiruddin Ruslananda (Problems and Perspectives in Management, 2018)
The present research aims to assess the influence of supervisor and colleague support on employee safety voice based on the social exchange theory and the effect of employee safety voice on employees’ satisfaction towards the organization. The data were collected from 302 bus drivers in Java, Indonesia. The data were then processed using a multiple regression analysis technique. The results indicate that supervisors have a significant negative effect on the action of voicing safety concerns by employees, while coworkers do not have any significant effect in relation to employees voicing their safety concerns. Furthermore, employee safety voice has also been found to have a significant negative effect on employee satisfaction towards their company.